INDONESIAN SAVINGS AND LOAN COOPERATIVES: DETERMINANTS of FINANCIAL STATEMENT QUALITY - Sari Mujiani; Patriandari; Moh. Abdurrosyid (Fakultas Ekonomi dan Bisnis Universitas Pancasila Jakarta, 2025)
This study investigates the growing emphasis on sustainability and ethical business practices by examining the influence of ESG scores, corporate governance, and corporate social responsibility (CSR) on financial statement quality in Indonesian savings and loan cooperatives. In recent years, cooperatives have been increasingly expected to adopt transparent and accountable practices aligned with sustainable development goals. However, the adoption of ESG principles and CSR initiatives, as well as the implementation of robust governance mechanisms, remains inconsistent across the sector. This gap raises concerns about the credibility and reliability of financial reporting within cooperatives, which are vital institutions for financial inclusion and community development. By exploring how these three elements contribute to enhancing financial transparency and stakeholder trust, the study highlights the need for integrated sustainability frameworks tailored to the cooperative context. The findings suggest that adopting ESG, strengthening governance, and implementing meaningful CSR programs can improve the quality of financial reports and promote long-term organizational resilience. These insights are valuable for cooperative leaders and policymakers aiming to strengthen trust, accountability, and sustainability within the cooperative sector.